Empirical Modeling the Effects of Cutting Parameters in High-Speed End Milling of Hardened AISI D2 under MQL Environment - Igbal, Asif; He, Ning; Li, Liang (Int Assoc Engineers-Iaeng, 2011)
In high-speed milling (HSM) of the hardened steels, the reduced tool life has always been a concerning issue. Moreover, in the case of finish HSM, the requirement of minimizing the workpiece surface roughness also gains considerable importance. In this research work, series of experiments were conducted in order to quantify the effects of three cutting parameters namely: cutting speed; feed rate; and radial depth of cut upon tool life and surface roughness. In total, 16 experiments were conducted following Central Composite Rotational Design (CCRD) Method. The machining of AISI D2 (similar to 62HRc) was performed using TiAlN coated carbide cutters, under MQL environment. The experimental data were used to develop empirical models for determining performance measures. Application of MQL was proved beneficial for enhancement of tool life. SEM photographs and EDS analyses revealed that chipping and adhesion were the dominant tool damage mechanisms in majority of the experiments.
World Congress on Engineering (WCE 2011) -- JUL 06-08, 2011 -- Imperial Coll, London, UNITED KINGDOM
Keywords: Empirical modeling; tool life; hardened steels; MQL; surface roughness